Liver and Kidney Function Biomarkers, Blood Cell Traits and Risk of Severe COVID-19: A Mendelian Randomization Study - Wang, Kai; Qu, Minghan; Ding, Lin; Shi, Xian; Wang, Chaolong; Cheng, Shanshan; Hao, Xingjie (Frontiers in Genetics, 2021)
The pandemic of Coronavirus disease 2019 (COVID-19) has posed an enormous threat to human health. According to observational studies, abnormal liver and kidney functions and blood cell traits were associated with severe COVID-19, yet the causal risk factors for COVID-19 severity and the underlying mechanism remained elusive. We performed Mendelian randomization analyses to assess the potential causal role of eight liver function biomarkers, one kidney function biomarker, and 14 hematological traits on COVID-19 severity using genetic association summary statistics from Europeans. Our findings showed that albumin, direct bilirubin, white blood cell count, neutrophil count, lymphocyte count, and mean corpuscular hemoglobin are casually associated with the risk of severe COVID-19. Notably, lymphocyte count and mean corpuscular hemoglobin had an independent effect on severe COVID-19 risk. These causal evidences provide insights into directions for the risk stratification of individuals with abnormal liver function or blood cell indices and motivate more studies to unveil the roles of these abnormalities in COVID-19 pathogenesis.